Effect of an electric vehicle mode in a plug-in hybrid electric vehicle with a post-transmission electric motor. (2016) - Foust, Travis; Jones, Ryan; Graves, Evan; McCoskey, Joshua; Yoon, Hwan-Sik
The additional design consideration of a plug-in hybrid electric vehicle (PHEV) caused by its recharging capability requires an optimal hybrid powertrain control strategy to fully exploit the vehicle's capability. Amongst many aspects of control algorithm development and design optimisation, the advantage of including a pure electric vehicle (EV) mode in the vehicle driving modes of a PHEV with a post-transmission electric motor was studied in this research. For this purpose, architecture of a series-parallel PHEV was determined and its simulation model was developed. Then, various simulations were conducted to evaluate technical merits of the pure EV mode in terms of fuel economy and emissions. The simulation results favourably supports inclusion of the pure EV mode as one of the driving modes in the powertrain control strategy of the studied PHEV model with a post-transmission electric motor.